SHEAR BOND STRENGTH OF ETCH AND RINSE ADHESIVES TO DENTIN: COMPARISON OF BOND STRENGTH AFTER ACID AND PAPACARIE PRE-TREATMENT - Sajjad, Mehvish; Munir, Nadia; Inayat, Naveed; Qaiser, Aneela; Wajahat, Mehreen; Wahad Khan, Mahwish (Journal of Ayub Medical College Abbottabad, 2021)
Background: Papacarie pre-treatment of dentin surface has been reported to exhibit good bond strength values between dentin and composites. Its desirable properties like high pH, sites specify and anti-inflammatory response makes it a future material in place acid etching pre-treatment. Acid etching may cause sensitivity and collapse of dentinal matrix. Methods: This in-vitro study involved, 60 caries free extracted premolars, randomly divided into three groups. Control Group (Group A) No pre-treatment of dentin prior adhesive application. Experimental Group B acid etchant was applied before adhesive application. Experimental Group C Papacarie was used as a pre-treatment agent. All these specimens were tested for shear bond strength with the help of Universal Testing Machine. All the collected data was entered in SPSS version 20.0. ANOVA was used to determine the mean SBS (Shear Bond strength) values of control and experimental groups. Results The mean shear bond strength of material was 7.74±0.47 in group A, 17.80±1.43 in group B and 15.11±0.70 in group C. Group B showing better strength than other two groups. Conclusion: The study provides information about longevity of composite restorations and may help in extending the clinical usage of papacarie to avoid harmful effects of acid etching on dentin and pulpal tissue.